Adjuvant Radiation Treatment of Breast Cancer After Mastectomy: Advanced Algorithms and Partial Bolus Improve the Dose Calculation Accuracy in the Case of Thin-Chest-Wall Irradiation - Dan Lundstedt, MD; Andreas Lindberg, MSc; Magnus Gustafsson, MSc; Roumiana Chakarova, PhD; Per Karlsson, MD (Advances in Radiation Oncology, 2023)
Purpose: The aim of this study was to examine measured and calculated dose distributions in a thin-chest-wall phantom and estimate the variations in the dose-volume histogram (DVH) parameters used in plan evaluation for patient geometries with chest-wall thicknesses <15 mm with and without bolus implementation. Methods and Materials: Measurements were made using thermoluminescent dosimeters in a chest-wall phantom. The Monte Carlo method, anisotropic analytical algorithm, and Acuros XB Eclipse algorithms were used to calculate dose distributions for clinical plans. DVH parameters for clinical target volume tumor (CTVT) and planning target volume (PTV) and mean doses were evaluated for 15 patients with a chest-wall thickness of 8 to 15 mm with and without partial bolus and for 10 patients with a chest-wall thickness of 20 to 25 mm without bolus. Results: Measurements showed that the dose at a depth of 2 to 12 mm at the beam entrance and laterally was within 90% of the dose at 8 mm depth. Monte Carlo and Acuros XB calculations were well aligned with the experimental data, whereas the anisotropic analytical algorithm underestimated the beam entrance and lateral doses. The DVH parameters for the patients with a thin chest wall were sensitive to calculation algorithm, resolution, body structure definition, and patient geometry. The parameters CTVTV95%, CTVTD98%, and PTVD98% were much lower than the tolerance criteria. Partial bolus improved the values for all algorithms and decreased the variations due to patient geometry. Dose calculations for patients with a chest-wall thickness of 20 to 25 mm resulted in sufficient target coverage and low dependence on patient geometry and calculation algorithm without the use of bolus. Conclusions: Dose calculations using advanced algorithms and resolution <2 mm are recommended for patients with a thin chest wall. Specific DVH criteria or the implementation of partial bolus was needed to facilitate plan development and evaluation for this patient group.